Proposal for a Controlled Humidity Environment Test Bench for the Accurate Characterization of Icephobic Properties - Louise Burdin; Anne-Catherine Brulez; Radoslaw Mazurczyk; Jean-Louis Leclercq; Stéphane Benayoun (Micromachines)
The accumulation of ice on equipment exposed to low temperatures raises major efficiency and safety concerns. To overcome this challenge, various strategies have been developed to create icephobic surfaces. Their characterization typically relies on the measurements of icing delay time (IDT) or ice adhesion strength. However, the absence of standardized testing equipment leads to significant variability, as each research group employs different setups and conditions. This lack of standardization complicates the comparison of results and the evaluation of surface performance. Herein, we describe the development of a new reproducible test bench that allows for simultaneous measurement of ice adhesion strength and IDT under controlled humidity conditions. Results reveal that increasing humidity leads to higher adhesion and lower IDT values. This study highlights the critical influence of humidity and suggests that tests should be performed at low humidity levels in order to accurately assess the intrinsic icephobic properties of surfaces.